Stimulation of morphofunctional repair of the facial nerve with photobiomodulation, using the end-to-side technique or a new heterologous fibrin sealant - Rosso, Marcelie Priscila de Oliveira; Rosa Júnior, Geraldo Marco; Buchaim, Daniela Vieira; German, Iris Jasmin Santos; Pomini, Karina Torres; de Souza, Rafael Gomes; Pereira, Mizael; Favaretto Júnior, Idvaldo Aparecido; Bueno, Cleuber Rodrigo de Souza; Gonçalves, Jéssica Barbosa de Oliveira; Ferreira Júnior, Rui Seabra [UNESP]; Barraviera, Benedito [UNESP]; et al. (Elsevier, 2017)
This research evaluated the influence of Photobiomodulation Therapy (PBMT) on lesions of the facial nerve repaired with the end-to-side technique or coaptation with a new heterologous fibrin sealant. Thirty-two Wistar rats were separated into 5 groups: Control group (CG), where the buccal branch of the facial nerve was collected; Experimental Suture Group (ESG) and Experimental Fibrin Group (EFG), in which the buccal branch was end-to-side sutured to the zygomatic branch on the right side of the face or coaptated with fibrin sealant on the left side; Experimental Suture Laser Group (ESLG) and Experimental Fibrin Laser Group (EFLG), in which the same procedures were performed as the ESG and EFG, associated with PBMT (wavelength of 830 nm, energy density 6.2 J/cm2, power output 30 mW, beam area of 0.116 cm2, power density 0.26 W/cm2, total energy per session 2.16 J, cumulative dose of 34.56 J). The laser was applied for 24 s/site at 3 points on the skin's surface, for a total application time of 72 s, performed immediately after surgery and 3 times a week for 5 weeks. A statistically significant difference was observed in the fiber nerve area between the EFG and EFLG (57.49 ± 3.13 and 62.52 ± 3.56 μm2, respectively). For the area of the axon, fiber diameter, axon diameter, myelin sheath area and myelin sheath thickness no statistically significant differences were found (p < 0.05). The functional recovery of whisker movement occurred faster in the ESLG and EFLG, which were associated with PBMT, with results closer to the CG. Therefore, PBMT accelerated morphological and functional nerve repair in both techniques.
Keywords: Facial nerve; Fibrin tissue adhesive; Low-level laser therapy; Nerve regeneration